Herwig Kogelnik [biography]. - Savage, N. (IEEE spectrum)
This paper presents a biographical overview of the 2001 IEEE Medal of Honor recipient, Herwig Kogelnik, who is recognized for his pioneering research and leadership in developing lasers and optoelectronics